Life cycle and population parameters of Sympherobius barberi Banks (Neuroptera: Hemerobiidae) reared with Dactylopius opuntiae Cockerell (Hemiptera: Dactylopiidae) - Pacheco-Rueda, Iliana; Lomelí-Flores, J. Refugio; Rodríguez- Leyva, Esteban; Ramírez- Delgado, Manuel (Instituto de Ecología, A.C., 2011)
Prickly pear Opuntia ficus-indica, is consumed in Mexico as young pads which are called nopalitos. It is a horticultural crop of great economical, social, and environmental importance. One of its most important pests is the wild cochineal insect, Dactylopius opuntiae. Amoung natural enemies of the latter are Sympherobius barberi, a predaceous brown lacewing that is considered one of the control alternatives. The objective of this research was to assess the biology of S. barberi reared on D. opuntiae. All the specimens used to establish laboratory colonies of both, pest and the predator, were collected during 2008 and 2009 from the nopalitos producing zone in Tlalnepantla, Morelos. S. barberi completed its life cycle in 28 days. Females had a four day preovipositional period, while daily average eggs per female was 1.98. Also, S. barberi had a net reproductive rate (Ro) of 36.6; a daily intrinsic rate of increase (rm) of 0.081; a generation time (T) of 44.27 d, and a finite reproductive rate (?) of 1.084.